Isolated/non-isolated quad-inverter configuration for multilevel symmetrical/asymmetrical dual six-phase star-winding converter - Padmanaban, Sanjeevikumar; Hontz, Michael R.; Khanna, Raghav; Wheeler, Patrick William; Blaabjerg, Frede; Ojo Olorunfemi, Joseph (2016)
This article presents the developments of a novel isolated/non-isolated quad inverter configuration for multilevel dual six-phase (twelve-phase) star-winding converter. The modular circuit consists of four standard voltage source inverters (VSIs). Each VSI is incorporated with one bi-directional switch (MOSFET/IGBT) per phase and links with the neutral line through two capacitors which allows symmetrical and asymmetrical operations. A modified single carrier five-level modulation (MSCFM) algorithm is developed and modulates each 2-level VSI as a 5-level output multilevel inverter. The entire AC converter is numerically modeled using Matlab/PLECS simulation software and the predicted behavior of the system is analyzed and presented. Good agreement is obtained between these results and the theoretical analysis. Suitable applications for the converter include (low-voltage/high-current) medium power systems, electrical vehicles, AC tractions, and ‘More-Electric Aircraft’ propulsion systems.